RETRACTED ARTICLE: Study on the mechanical behavior of construction and demolition waste-based geopolymers under high-temperature conditions - Yiming Chen (Journal of Asian Architecture and Building Engineering)
Statement of Retraction: Study on the mechanical behavior of construction and demolition waste-based geopolymers under high-temperature conditions We, the Editors and Publisher of Journal of Asian Architecture and Building Engineering, have retracted the following article: Yiming Chen (2025) Study on the mechanical behavior of construction and demolition waste-based geopolymers under high-temperature conditions, Journal of Asian Architecture and Building Engineering, 2025; 24(2): 650–665. DOI: 10.1080/13467581.2024.2308595. Since publication, significant concerns have been raised about the fact that this article has substantial overlap with the following article, Ioanna Giannopoulou, Ponsian M. Robert, Michael F. Petrou, Demetris Nicolaides (2024) Mechanical behavior of construction and demolition waste-based alkali activated materials exposed to fire conditions, Construction and Building Materials, DOI: 10.1016/j.conbuildmat.2024.134994 Upon query, the author has not been able to provide a satisfactory explanation for this significant level of overlap. As this is a serious breach of our Editorial Policies, we are retracting the article from the journal. The author has been informed of this decision. We have been informed in our decision-making by our editorial policies and the COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.